Qualitative analysis of narratives about private apparitions of the Virgin Mary in the Roma community as an example of polyphonic ethnography - Zachar Podolinská, Tatiana (Romano džaniben, 2018)
The overall research dataset used for the purposes of this paper is part of ongoing research of the author on Roma folk beliefs (2006-2007), as well as on the activities of both traditional and non-traditional religious movements among the Roma in Slovakia (2003-2011). The study offers an in-depth qualitative analysis of a narrative on private Marian apparitions of one Romani woman living in a segregated Roma settlement in Šariš region, Eastern Slovakia, using the interpretative-phenomenological analysis (IPA, Smith et al. 2009). In order to offer the reader a holistic picture of research situation, the author uses not only the qualitative analysis and thematic coding, but also the perspective of multivocal ethnography (Tobin 1988; Clegg 2017). The interview is thus embedded in the synchronous context of field journal notes of the author, as well as in the diachronic context of her recent memories. The qualitative analysis also includes a wider context of the thematic search of media reports on local apparitions among Roma households in Eastern Slovakia. Based the Bachtin’s concept of polyphony and dialogism, the author discusses also broader methodological point of the production of ethnological knowledge within synergic and creative triangulation of actors in terms of author – informant – reader.